Pengaruh Faktor-Faktor Fundamental Mikro Terhadap Return Saham Pada Perusahaan Transportasi Yang Terdaftar Pada Bursa Efek Indonesia - Bambang Suhada; Karnila Ali; Nurul Fitriani (Universitas Muhammadiyah Metro, 2024)
This research aims to analyze and test the influence of micro-fundamental factors on stockreturns. This Research Is A Quantitative Research Using A Sampling Technique Method ThatObtains 12 Sample Companies. The population of this study are transportation companieslisted on the Indonesia Stock Exchange which are continuously issuing financial reports from2016-2020. This Research Uses Secondary Data Obtained from www.idx.co.id. This analysismethod uses panel data regression and classical assumptions. The results of this studyindicate that the micro-fundamental factors for stock returns have a T-test value (Fstatistic)of 0.476295 > 0.005. While the F test shows the influence value is -0.008064 <0.00. Fromthe calculation of the R value, the results of the determination test conducted in this studyresulted in an r value in the upper table of x1 = 0.1309, where the r value was > 0.005 andwas declared to have no effect. X2 = 0.7900 where the value of r > 0.005 means it has noeffect. X3 = 0.6598 where the value of r > 0.005 means it has no effect.